Direct observation of the enhancement of noncooperative protein self-assembly by macromolecular crowding: Indefinite linear self-association of bacterial cell division protein FtsZ - Rivas, Germán (The National Academy of Sciences, 2001)
Recent measurements of sedimentation equilibrium and sedimentation velocity have shown that the bacterial cell division protein FtsZ self-associates to form indefinitely long rod-like linear aggregates in the presence of GDP and Mg(2+). In the present study, the newly developed technique of non-ideal tracer sedimentation equilibrium was used to measure the effect of high concentrations—up to 150 g/liter—of each of two inert “crowder” proteins, cyanmethemoglobin or BSA, on the thermodynamic activity and state of association of dilute FtsZ under conditions inhibiting (−Mg(2+)) and promoting (+Mg(2+)) FtsZ self-association. Analysis of equilibrium gradients of both FtsZ and crowder proteins indicates that, under the conditions of the present experiment, FtsZ interacts with each of the two crowder proteins essentially entirely via steric repulsion, which may be accounted for quantitatively by a simple model in which hemoglobin, albumin, and monomeric FtsZ are modeled as effective spherical hard particles, and each oligomeric species of FtsZ is modeled as an effective hard spherocylinder. The functional dependence of the sedimentation of FtsZ on the concentrations of FtsZ and either crowder indicates that, in the presence of high concentrations of crowder, both the weight-average degree of FtsZ self-association and the range of FtsZ oligomer sizes present in significant abundance are increased substantially.